2011
DOI: 10.1007/s10620-011-1931-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Taurine on Hepatic Steatosis Induced by Thioacetamide in Zebrafish (Danio rerio)

Abstract: Taurine seems to improve hepatic steatosis by reducing oxidative stress and increasing SIRT1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Continuous treatment with TAA for 12 weeks leads to development of hepatic fibrosis and induction of HCC (153). TAA-induced steatosis has been successfully treated by administration of taurine, which functions at least in part, by decreasing oxidative stress (65). …”
Section: Modeling Human Liver Disease Mechanisms In Zebrafishmentioning
confidence: 99%
“…Continuous treatment with TAA for 12 weeks leads to development of hepatic fibrosis and induction of HCC (153). TAA-induced steatosis has been successfully treated by administration of taurine, which functions at least in part, by decreasing oxidative stress (65). …”
Section: Modeling Human Liver Disease Mechanisms In Zebrafishmentioning
confidence: 99%
“…The increased level of serum ammonia in OHE mice was ascribed to the impairment of urea cycle, which normally removes ammonia from body. TAU supplement could ameliorate both liver dysfunction and encephalopathy disorder as revealed by decreased contents of serum ammonia, ALT and AST, and increased level of SOD (Dorgru-Abbasoglu et al 2001;Hammes et al 2012). Compared with CTRL mice, mice in OHE group showed poor ability of reflexes and task performance with significantly elevated NSS of OHE group at 72 h after TAA administration, revealing severely impaired brain function due to TAA intoxication.…”
Section: Discussionmentioning
confidence: 93%
“…(Color figure online) could ameliorate liver injury induced by TAA via its free radical scavenging activity Hammes et al 2012) and enhanced intracellular production of glutathione (GSH) (Das et al 2010). Overwhelmed by the TAA-induced oxidative stress, hepatic TAU and GSH were largely consumed and significantly decreased in OHE group as a self-defense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish are indeed able to respond to LPS, however with much lower sensitivity than mammals and via a tlr4/myd88 -independent signaling pathway[24,28]. Among the few studies that evaluated tnf-a expression in the liver of zebrafish, Sapp observed an elevation of tnf-a in fructose-treated larvae and Hammes in thiocetamide-treated fish[20,29]. Although there was no direct evidence in our study, these cited findings conducted us to the following conclusions: tnf-a is not promptly induced by LPS in zebrafish exposed to ethanol as occurring in mammals and its activation mechanism seems to be associated to more aggressive hepatotoxicants.…”
Section: Discussionmentioning
confidence: 99%
“…To date, very few data are available regarding the effect of chronic ethanol exposure on hepatic adipor2 . Hammes et al[29] observed decreased mRNA expression of hepatic adipor2 and sirt-1 and increased tnf-a in a model of NAFLD induced by thioacetamide in zebrafish. Possibly, thioacetamide, a more aggressive liver toxicant, contributed to down regulate adipor2 .…”
Section: Discussionmentioning
confidence: 99%